2013
DOI: 10.1002/bip.22162
|View full text |Cite
|
Sign up to set email alerts
|

The activity of prolactin releasing peptide correlates with its helicity

Abstract: The prolactin releasing peptide (PrRP) is involved in regulating food intake and body weight homeostasis, but molecular details on the activation of the PrRP receptor remain unclear. C-terminal segments of PrRP with 20 (PrRP20) and 13 (PrRP8-20) amino acids, respectively, have been suggested to be fully active. The data presented herein indicate this is true for the wildtype receptor only; a 5-10-fold loss of activity was found for PrRP8-20 compared to PrRP20 at two extracellular loop mutants of the receptor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Two isoforms of PrRP with either 20 or 31 amino acids sharing identical C-termini showed comparable in vitro and in vivo activity [1]. Several SAR studies with PrRP analogs were performed [31,56,57,58]. No study about selective antagonists of PrRP has been published yet, but in 2010, Otsuka Pharmaceuticals patented nonpeptide heterocyclic antagonists derived from tetrahydropyridol [4,3-d]pyrimidinone developed for stress-related diseases (reviewed in [59]).…”
Section: Structure-activity Relationship Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Two isoforms of PrRP with either 20 or 31 amino acids sharing identical C-termini showed comparable in vitro and in vivo activity [1]. Several SAR studies with PrRP analogs were performed [31,56,57,58]. No study about selective antagonists of PrRP has been published yet, but in 2010, Otsuka Pharmaceuticals patented nonpeptide heterocyclic antagonists derived from tetrahydropyridol [4,3-d]pyrimidinone developed for stress-related diseases (reviewed in [59]).…”
Section: Structure-activity Relationship Studiesmentioning
confidence: 99%
“…DeLuca et al performed a structural study based on NMR and CD spectroscopy, where they determined the α-helical conformation in trifluoroethanol of the C-terminal sequence of PrRP20 [57]. Shorter PrRP20 analogs, PrRP(4–20), PrRP13 (PrRP(8–20)), and heptapeptide PrRP(14–20), decreased the stability of the helical segment and their biological activity was reduced.…”
Section: Structure-activity Relationship Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors’ models were supported by CD data collected in water, dodecylphosphocholine micelles, SDS micelles, and TFE. For both forms of ghrelin, the helicity increased significantly in SDS micelles and TFE [ 23 ] A similar trend was observed for the prolactin releasing peptide (PrRP), another peptide that plays a role in food intake and body weight homeostasis [ 85 ]. In the case of PrRP, it was demonstrated that the peptide likely exists in a conformational equilibrium between α- and 3 10 -helix, and the helical propensity of the peptide is essential for its ability to activate the PrRP receptor, another GPCR.…”
Section: Discussionmentioning
confidence: 73%
“…Several peptide hormones have been examined to understand their structure via NMR or CD in solution. These include motilin [ 146 ], prolactin-releasing peptide [ 147 , 148 ], vasopressin [ 149 ], relaxin [ 150 , 151 ], and somatostatin analogues [ 152 , 153 , 154 , 155 ]. In contrast, relatively few examples of peptides exist, which are studied in both their solution and bound states.…”
Section: Implications For Future Studiesmentioning
confidence: 99%